EVALUATING EDUCATIONAL MATERIALS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This research examines systematic approaches to evaluating educational materials, focusing on the criteria and methodologies that ensure pedagogical effectiveness and alignment with learning objectives. The study analyzes how comprehensive evaluation frameworks can enhance material selection processes while promoting student engagement and educational outcomes across diverse learning environments.